Effect of platelet activating factor (PAF) on protein tyrosine phosphorylation during acrosome reaction of buffalo spermatozoa - GARG, MONIKA; VEDANTAM, SIVARAM; MOHANARAO, G JAGAN; ATREJA, S K (The Indian Journal of Animal Sciences, 2012)
Ejaculated spermatozoa must undergo 2 important preparatory changes namely capacitation and acrosome reaction to be able to fertilize an egg. Among the biochemical changes that take place during capacitation and acrosome reaction, protein tyrosine phosphorylation has been considered as an important event associated with different sperm functions. PAF (1-O-alkyl-2-acetyl-sn-glycero-3-phophocholine), a potent signaling phospholipid, also regulates different sperm maturational processes. This study was undertaken to determine the effect of different concentrations of PAF as well as its incubation time on protein tyrosine phosphorylation during acrosome reaction of buffalo spermatozoa. Number of protein substrates were tyrosine phosphorylated and their degree of phosphorylation increased with increase in concentrations of PAF. However at higher concentrations of PAF (500 nM) a significant decrease in the extent of tyrosine phosphorylation was observed with respect to 20, 25 and 40 kDa proteins. It was also observed that with the increase in PAF incubation time the degree of protein tyrosine phosphorylation increased during acrosome reaction of buffalo spermatozoa. In conclusion, the effect of PAF on the extent of tyrosine phosphorylation of sperm proteins appeared to be dose related and time dependent and this compound can be utilized for the induction of acrosome reaction in buffalo spermatozoa.